User Cost and the Preference Function - Latham, R. W.; Peel, D. A. (Quarterly Journal of Economics, 1975)
Journal Article User Cost and the Preference Function Get access R. W. Latham, R. W. Latham University of Liverpool Search for other works by this author on: Oxford Academic Google Scholar D. A. Peel D. A. Peel University of Liverpool Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 89, Issue 1, February 1975, Pages 154–156, https://doi.org/10.2307/1881718 Published: 01 February 1975